Pengaruh LTDER, Ukuran Perusahaan, Dan Keputusan Investasi Terhadap Nilai Perusahaan - Diahnisa Indriasari; Eko Widodo; Trisnia Widuri (Institut Nalanda, 2023)
This research was conducted to explain the effect of Long Term Debt to Equity Ratio (LTDER), firm size and investmen decision to firm value on companies sub sector cement which listed on the Indonesia Stock Exchange in 2015-2022. This type of research is quantitative with used secondary data from annual financial reports. The sampling technique used purposive sampling. The sample this study was 32 financial reports on companies sub sector cement in the 2015-2022 period. The analysis technique used panel data regression analysis. The results of this research showed that Long Term Debt to Equity Ratio (LTDER) had no significant negative effect on firm value, firm size had a significant positive effect on firm value, investmen decision had a significant positive effect on firm value, and Long Term Debt to Equity Ratio (LTDER), firm size, investmen decision simultaneously had a significant effect on firm value.